Insight Into the Dynamics of the Rabinowitsch Fluid Through an Elliptic Duct: Peristalsis Analysis - Nadeem, Sohail; Abbas Haider, Jamil; Akhtar, Salman; Mohamed, Abdullah (Frontiers in Physics, 2022)
The current research is concerned with the mechanical characteristics of a Rabinowitsch fluid model that has been developed via an elliptic duct. If you study physiology or biomedicine, you'll find the Rabinowitch fluid model in peristalsis very useful because it is used to move blood around in the heart, lungs, sanitary fluid transport systems, transfer of corrosive fluids, and innovative pharmaceutical delivery systems. It is possible to get elliptic domain for this duct model by using cartesian coordinates, and in the boundary conditions for this duct, the equation of ellipse is used to keep the elliptic cross section for this duct in place. A mathematical model for an incompressible fluid is being created, and the mathematical issue is then transformed into its dimensionless form by using suitable transformations, including long wavelength approximation. As soon as the problem is put into a dimensionless form, the partial differential equations for the velocity profile can be found. These partial differential equations are solved across the elliptic cross sections with the help of boundary conditions that are given, and accurate mathematical solutions are then found for them.